THE LIVING OF PUERPERAS IN FRONT OF NURSING ASSISTANCE RECEIVED DURING THE PUERPERAL GRAVID CYCLE - Rodrigues Carvalho, Nayara; Fernandes Arial Ayres, Lilian; Andrade e Silva, Erika; Véo Nery de Jesus, Mariana (LINKSCIENCEPLACE, 2026)
Descriptive research, with qualitative approach, whose subjects were 13 puerperal residents in the city of Viçosa (MG). The aim of this study was to analyze the experience of puerperal women in the context of Primary Health Care in the municipality of Viçosa, Minas Gerais State, Brazil, in response to nursing care received during the puerperal pregnancy cycle. Given the significance at this time it is necessary to biologically, socially and emotionally prepare both the pregnant woman and the family. The data were obtained from November 7, 2014 to May 13, 2015, through a semi-structured interview, which were interpreted using the Bardin content analysis technique. The results highlight that the puerperas consider the nurse only for the resolution of administrative and bureaucratic procedures. Emphasis is given to the constant presence of nursing academics from the Federal University of Viçosa. Thus, it is necessary (re) to think and plan nursing care practices applied at this time of life to improve the care provided to both the woman and the family.